Pairing status and stimulus type predict responses to audio playbacks in female titi monkeys - Lau, Allison R.; Cunningham, Ashley D.; Bales, Karen L. (Frontiers in Ecology and Evolution, 2023)
Some paired primates use complex, coordinated vocal signals to communicate within and between family groups. The information encoded within those signals is not well understood, nor is the intricacy of individuals' behavioral and physiological responses to these signals. Considering the conspicuous nature of these vocal signals, it is a priority to better understand paired primates’ responses to conspecific calls. Pair-bonded titi monkeys (Plecturocebus cupreus) sing duets comprised of the male and female’s long call. Here, we use a playback study to assess female titi monkeys’ responses to different vocal stimuli based on the subject’s pairing status. Six adult female titi monkeys participated in the study at two timepoints––pre-pairing and post-pairing. At each timepoint, subjects underwent three distinct playbacks––control recording, male solo vocalization, and pair duet. Behaviors such as locomotion and vocalizations were scored during and after the playback, and cortisol and androgen values were assessed via a plasma blood sample. Female titi monkeys attended more to social signals compared to the control, regardless of pairing status. However, in the time immediately following any playback type, female titi monkeys trilled more and spent a greater proportion of time locomoting during pre-pairing timepoints (compared to post-pairing). Female titi monkeys’ behavioral responses to social audio stimuli, combined with subjects’ increases in cortisol and androgens as paired individuals, imply female titi monkeys attend and respond to social signals territorially.